The Effect of Prospective Bride Counseling Program on the Attitudes of Prospective Brides in Preparing for a Healthy Pregnancy at the Tilamuta Community Health Center - Retno Dewi Prisusanti; Amalia A. Mootalu (Institut Nalanda, 2024)
Healthy pregnancy preparation is a crucial aspect of maternal and child health, and premarital counseling programs are designed to support prospective couples in achieving this goal. This study aimed to examine the effect of the CATIN premarital counseling program on the attitudes of prospective brides and grooms toward healthy pregnancy preparation at Puskesmas Tilamuta. A quasi-experimental design with pre-test and post-test control group was employed. The study involved 60 participants, divided equally into an intervention group receiving structured counseling and a control group receiving routine health information. Data were collected using a validated questionnaire measuring attitudes toward nutrition, lifestyle, reproductive health knowledge, and readiness for preconception care. Data analysis was performed using descriptive statistics, paired t-tests, and independent t-tests with a significance level of p < 0.05. The findings indicated a significant improvement in attitude scores in the intervention group, with the mean increasing from 65.2 ± 5.8 in the pre-test to 78.6 ± 6.1 in the post-test (p < 0.001). In contrast, the control group showed a minimal, non-significant increase from 64.8 ± 6.2 to 66.0 ± 5.9 (p = 0.102). The independent t-test confirmed a significant difference between groups in post-test scores (p < 0.001), demonstrating the effectiveness of the structured CATIN counseling program in enhancing prospective couples’ attitudes toward healthy pregnancy preparation. In conclusion, structured premarital counseling positively influences attitudes and readiness for preconception health, supporting better maternal and neonatal outcomes. Implementation of such programs in community health centers is recommended to strengthen preventive reproductive health services.